2019
DOI: 10.5723/kjcs.2019.40.2.115
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Maternal Childhood Attachment and Paternal Involvement in Child-Rearing and Maternal Parenting Efficacy on Parenting Behavior of Mothers with Infants

Abstract: Objectives: The main purpose of this study was to examine direct effects of maternal childhood attachment and paternal involvement on parenting behavior, and indirect effects through maternal parenting efficacy. Methods: A total of 310 participants, mothers of 6-to 15-month-old infants, responded to questionnaires, which included items related to maternal childhood attachment, paternal involvement, maternal parenting efficacy, and parenting behavior. Data were analyzed by using structural equation modeling (SE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…The father's sensitivity is a modifiable factor. Recent studies have confirmed that caregivers’ sensitivity could be enhanced by a parent-child interaction intervention program that provides expert advice on improving their interactive behavior based on video-recorded interactions between caregivers and children [ 9 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The father's sensitivity is a modifiable factor. Recent studies have confirmed that caregivers’ sensitivity could be enhanced by a parent-child interaction intervention program that provides expert advice on improving their interactive behavior based on video-recorded interactions between caregivers and children [ 9 , 11 ].…”
Section: Introductionmentioning
confidence: 99%